Early functional and therapeutic effect of reversed tumour shoulder prosthesis reconstruction after proximal humerus tumour resection - Wang, Shang; Luo, Yi; Wang, Yitian; Zhang, Yuqi; Gong, Taojun; Tu, Chongqi; Zhou, Yong (Frontiers in Surgery, 2022)
Introduction: Reconstruction of proximal humeral tumours after resection is still controversial. And there are few articles describing oncology patients' postoperative function after reversed tumour shoulder prosthesis reconstruction. We investigated the functional results of patients who underwent reversed tumour shoulder prosthesis, including those who did not preserve the deltoid ending point. Patients and methods: We retrospectively evaluated 16 patients with proximal humerus tumours who had undergone reversed tumour shoulder prosthesis. All patients underwent type Malawer I proximal humeral resection surgery and standard reverse tumour shoulder arthroplasty with a modular reverse shoulder prosthesis. We sutured the severed end of the deltoid to the brachialis muscle using the artificial patch for patients who had their deltoid ending point resected. Patients are rehabilitated and followed up according to our instructions. Result: All patients were followed up for a mean of 27.4 months (13 to 59), and their mean age was 45.9 years (15 to 74). The mean length of the humeral resection was 11.6 cm (5-15). The mean shoulder mobility was 122° (82° to 180°) in forward flexion; 39° (31° to 45°) in posterior extension; 102° (65° to 172°) in abduction; 43° (30° to 60°) in external rotation; 83° (61° to 90°) in internal rotation, and a mean MSTS score of 77.9% (63.3% to 93.3%). The mean DASH score was 20.8 (2.5 to 35.8). The mean VAS score was 0.9. For patients who had their deltoid ending point resected, the mean length of the humeral resection was 14.0 cm; the mean shoulder mobility was 109° in forward flexion; 37.8° in posterior extension; 102.0° in abduction; 38.3° in external rotation; 86.3° in internal rotation, and the mean MSTS score was 78.8%; the mean DASH score was 21.6; the mean VAS score was 1.0. Conclusion: Patients who underwent reverse tumour shoulder arthroplasty can achieve good early postoperative function, survival rate and low complication rate. In addition, patients who had their deltoid ending point removed also obtained good function after particular reconstruction.